Student perceptions on sustainable entrepreneurship: ecological, social, and cultural dimensions - Fatimah, Ai Tusi; Faridah, Didih; Dadi, Dadi; Ratnawati, Ratnawati (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This study examines students' perceptions on sustainable entrepreneurship within cultural diversity context in Asia, focusing on ecological, social, and cultural dimensions. By surveying 144 students from various faculties who attended an international public lecture, the research revealed a comprehensive understanding of sustainability among the participants. The analysis indicated a strong correlation among the three dimensions, suggesting that students view sustainability as an interconnected concept. However, the study also found significant differences in perceptions across different faculties, showing that educational background influences students' understanding on sustainability. These findings emphasize the need to integrate sustainability education into university curricula to equip students with the knowledge and skills necessary to become sustainable entrepreneurs. Additionally, the results of this study offer insights for developing entrepreneurship training programs that are more relevant to the Asian context, encouraging the establishment of businesses that positively impact society and the environment.